Watercolor - Clarke, Michael (New York : Dorling Kindersley, 2000)
A visual history of watercolor painting from its ancient beginnings to the works of modern masters.
Includes index.
Kirkus Starred.
Wilson's Senior High School.
7.0.
7.0
5-8
Keywords: Watercolor painting -- History -- Juvenile literature; Watercolor painting -- History; Watercolor painting -- History